Colombia : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of Colombia. (IMF Staff Country Reports; Country Report ;, 2010)
The key findings of Colombia's 2010 Article IV Consultation on economic developments and policies are presented. The Colombian economy had begun to slow down in early 2008, as policies had been tightened to address overheating, but the global crisis caused private investment to collapse in the last quarter of 2008. The largely domestically owned and locally financed financial system did not experience major strains from the global crisis. Colombian banks did not have complex off-balance sheet financial instruments, and had limited cross-border linkages.